A Review of Nanofluid Adoption in Polymer Electrolyte Membrane (PEM) Fuel Cells as an Alternative Coolant - Irnie, Zakaria; Z., Michael; W. A. N., W. Mohamed; A. M. I., Mamat; Azmi, W. H.; R., Mamat; R., Saidur (Faculty Mechanical Engineering, UMP, 2015)
Continuous need for the optimum conversion efficiency of polymer electrolyte membrane fuel cell (PEMFC) operation has triggered varieties of advancements, namely in the thermal management engineering scope. Excellent heat dissipation is correlated with higher performance of a fuel cell, thus increasing its conversion efficiency. This study reveals the potential advancement in thermal engineering of a fuel cell cooling system with respect to nanofluid technology. Nanofluids are seen as a potential evolution of nanotechnology hybridization with the fuel cell serving as a cooling medium. The available literature on the thermophysical properties of potential nanofluids, especially on the electrical conductivity property, has been discussed. The lack of electrical conductivity data for various nanofluids in open literature was another challenge in the application of nanofluids in fuel cells. Unlike in any other thermal management system, a nanofluid in a fuel cell is dealt with using a thermoelectrically active environment. The main challenge in nanofluid adoption in fuel cells was the formulation of a suitable nanofluid coolant with heat transfer enhancement, as compared to its base fluid, but still complying with the strict limits of electrical conductivity as low as 2 S/cm and several other restrictions discussed by the researchers. It is concluded that a nanofluid in PEMFC is advantageous in terms of both heat transfer and simplification of the cooling system through radiator size reduction and potential elimination of the deionizer as compared to the current PEMFC cooling system. However, there are challenges that need to be well addressed, especially in the electrical conductivity requirement.